Community of Sharks from Fishermen's Bycatch Landed at the Fishermen's Fish Market, Pondokdadap Coastal Fishing Port, Malang - East Jawa - Nur Laila Anggraini; Husain Latuconsina; Hamdani Dwi Prasetyo; Anthon Andrimida (BIOSAINSTEK, 2026)
Sharks are cartilaginous fish that play an important ecological role in marine ecosystems. However, their existence in the wild is very vulnerable to overfishing and habitat degradation. This study aims to identify species and analyze the structure of shark communities as bycatch of fishermen. This study was conducted from April to June 2025 at the Fishermen's Fish Market, Pondokdadap Beach Fishing Port Area, Sendangbiru, Malang, East Java, through observation of morphological characters and interviews as supporting data. Data analysis is descriptive in the form of Tables and Graphs. The results of fish identification include 17 individuals from 3 species representing 2 families from 2 orders, namely Chiloscyllium griseum, Squalus montalbani, and Squalus hemipinnis. All individuals caught are categorized as having entered the adult phase, so they are biologically suitable for capture. The diversity index (H') value is in the low category, the evenness index (E) is in the stressed category, and the dominance index (C) is in the high category. The low number of shark catches landed is due to the publicity of the shark trade ban by the Pondokdadap Coastal Fishing Port authorities and strict sanctions against violators. Despite this, some shark landings are still carried out illegally, reflecting low awareness among fishermen and fish traders, as well as high demand for sharks in the market. Efforts to conserve sharks from overfishing need to be continuously improved through intensive and widespread outreach to various stakeholders to build a shared understanding regarding shark conservation in the wild.